The vitamin D binding protein axis modifies disease severity in Lymphangioleiomyomatosis - Miller, Suzanne; Coveney, Claire; Johnson, Janice; Farmaki, Aliki-Eleni; Gupta, Nishant; Tobin, Martin D.; Wain, Louise V.; McCormack, Francis; Boocock, David J.; Johnson, Simon R. (European Respiratory Society, 2018)
Background: Lymphangioleiomyomatosis (LAM) is a rare disease of women. Decline in lung function is variable making appropriate targeting of therapy difficult. We used unbiased serum proteomics to identify markers associated with outcome in LAM.